An environmental impact assessment for the access road to the Mohale dam, Lesotho : a comparative analysis of the Western access road and the least cost alternative route - Schreiner, Barbara (Department of Environmental and Geographical Science, 2016)
The purpose of this document is to set out a comparison of the environmental impacts of the two alternative access roads to the Mohale Dam, Lesotho: the Least Cost Alternative Route (LCAR) and the Western Access Route (WAR), and to recommend a preferred alternative for construction. The analysis and comparison is couched in a theoretical framework with regard to the process, nature and function of Integrated Environmental Management (IEM) and the problems associated with implementation of the IEM process. In this report I1 set out some of the limitations and problems associated with the EIA on the access road to the Mohale Dam (LHDA Contract No 1000). I then discuss the criteria on which a selection of a preferred alternative should be made, focussing on concepts of sustainability (including ecological sustainability), provision of basic human needs, equity and social justice, and cultural diversity and self-realisation. Within the context framed by the limitations of this EIA, the report then compares the LCAR and the WAR, and makes recommendations with regard to a preferred alternative, based on this comparison. The report also provides comments and discussion on a management and monitoring plan for Phase lB of the Lesotho Highlands Water Project (LHWP).